Outcome of Optical Internal Urethrotomy and Anastomotic Uretrhoplasty for Short Segment Bulbar Urethral Stricture (Bangladesh Journal of Urology, 2020)
Background: Urethral stricture diseases are common urological problems in our country. The etiologies include iatrogenic, trauma, infection, congenital and very few are idiopathic. Urethral strictures have the potential for great negative impact on patients. These have several treatment modalities, ranging from simple dilations to complex multistaged urethroplasties. Optical internal urethrotomy and anastomotic urethroplasty are the common procedures among them which are particular topics in this study.Objectives: To evaluate the outcome of two surgical techniques- Optical Internal Urethrotomy (OIU) and Anastomotic Urethroplasty.Methodology: A total of 50 patients with short segment bulbar urethral strictures were consecutively included in the study. Purposive sampling method was applied. The present outcome clinical study was conducted in the department of Urology, National Institute of Kidney Diseases and Urology, Sher-E-Bangla Nagar, Dhaka, Bangladesh over a period of 1 year from February 2016 to January 2017. Student’s t-test and chi-square test were applied for hypothesis testing. ‘P’ value